Efficiency of compensatory growth of Borana bulls (Bos indicus) following different levels of feed restriction - Tolla, N.; Mirkena, T.; Yimegnuhal, A. (Informa UK Limited, 2002)
To study the efficiency of compensatory growth following different levels of feed restriction, 25 Borana bulls were blocked by weight and randomly allocated to five dietary treatments of ad libitum feeding for the entire period (control), maintenance feeding for 91 days (maintenance), 15 per cent weight loss in 91 days (-15%), 20 per cent weight loss in 91 days (-20%) and 25 per cent weight loss in 91 days (-25%) followed by 105 days of ad libitum (compensatory) feeding. The feed restriction imposed for treatments - 15 per cent, -20per cent and -25per cent during the initial period resulted in weight losses of -15 per cent, -19 per cent and -23 per cent, respectively. There was no significant (P>0.05) difference among treatments on feed intake during compensatory feeding period. Daily gain (ADG) for the restricted animals was directly proportional to the level of feed restriction. There was also significant (P<0.05) treatment effect on dressing percentage and proportion of fat in carcass. Animals subjected to weight losses of -15 per cent, -20 per cent and -25 per cent had lower yield of these carcass characteristics than the control and maintenance treatment. This study revealed that Borana bulls may not achieve complete compensation in 105 days of compensatory feeding, after 91 days of feed restriction below their daily maintenance requirement.